Pengaruh Kecerdasan Logis-Matematis terhadap Hasil Belajar Fisika Melalui Metode Pembelajaran Problem Solving - Indrawati Pamoras; Muhammad Ali; I Komang Werdhiana (Universitas Tadulako, 2021)
The study aimed to determine whether there was an influence of logical-mathematical intelligence on students' physics learning outcomes through the Problem Solving learning method. This type of research was quantitative research with the pre-experimental. The sampling technique was purposive sampling. The sample of this study was 29 students of class X MIPA 1. The research instrument was a logical-mathematical intelligence test and a physics learning outcome test. The results of the analysis of the correlation test between the variables X and Y obtained rxy = 0.41. This shows that the influence of logical-mathematical intelligence (X) on learning outcomes (Y) is in the medium category. The logical-mathematical intelligence test obtained showed that the average score of the pretest was 5.69 and the posttest was 19.13. Meanwhile, in the physics learning result test, it was obtained that the average score of the pretest was 10.93 and the posttest was 14.52. The results of simple linear regression analysis showed that the variation of logical-mathematical intelligence scores on learning outcomes with the estimated function Ÿ = 5.08 + 0.40X. Based on data analysis with a significance level of 5%, db for numerator 1 and db for denominator 27 obtained Fcount 5.36 > Ftable 4.21. So, it can be concluded that H0 is rejected, meaning that there is a positive and significant influence of logical-mathematical intelligence on the learning outcomes of physics through the Problem Solving learning method.